PENDEKATAN PARTISIPATIF KEPADA ORGANISASI PERANGKAT DAERAH DALAM INVENTARISASI SUMBERDAYA ALAM UNTUK KEBERLANJUTAN EKOSISTEM KABUPATEN BURU - Pattimahu, Debby; Soselisa, Fanny; Sahupala, Andjela; Parera, Evelin; Pattimahu, Terezia (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
Natural resource inventory is a crucial initial step in environmental management and protection planning. This activity is carried out with a participatory approach. Buru Regency has diverse natural resource potential, including forests, agricultural land, waters, and biodiversity that need to be managed sustainably. This activity aims to conduct a natural resource inventory to support the preparation of a scientific and participatory environmental management and protection plan. Evaluation of the results of the activity shows that there is a significant increase in the involvement of Regional Apparatus Organizations (OPD), increased participation (40% to 85%), data utilization for policy (30% to 80), increased capacity (35% to 82%), coordination of Regional Apparatus Organizations (OPD) for constraints and solutions (25% to 75%).